STRATEGI KEPEMIMPINAN ABAD 21: VISIONER, KREATIF, INOVATIF, DAN CERDAS EMOSI - Isnaini, Lailatul (UIN Imam Bonjol Padang, 2019)
The idea of 21st Century leadership goes from the view that leaders must recognize precisely and fully both about themselves and about the conditions and aspirations of the people they lead, the development and the strategic environmental problems encountered in various fields, especially in the field they do, as well as the paradigm And the organizational and management systems in which it plays a role. The leader's responsibility is to provide solutions wisely and precisely on the problems and challenges facing his time, which is done with the people he leads. Organizational leaders occupy a central position in the effort to promote their institutions. Therefore, one of the things that a leader must have is creativity and innovation of his organization,Â an effort to make positive new breakthroughs that make the organization better, more advanced and ready to face the 21st century. In addition to having a vision and intelligent Intelligently, leaders are also required to have other intelligence in the face of the complexity of the current problems are increasingly difficult to overcome, namely emotional intelligence (EI).Â